1784 N.Y. Laws 627, An Act to Prevent the Danger Arising from the Pernicious Practice of Lodging Gun Powder in Dwelling Houses, Stores, or Other Places within Certain Parts of the City of New York, or on Board of Vessels within the Harbour Thereof, ch. 28. - (:unkn) unknown (General Publisher, 1784)
it shall not be lawfull [sic] for any merchant, shopkeeper, or retailer, or any other person, or persons whatsoever, to have or keep any quantity of gun powder exceeding twenty-eight pounds weight, in any one place, less than one mile to the northward of the city hall of the said city, except in the public magazine at the Fresh-water, and the said quantity of twenty-eight pounds weight, which shall be lawfull [sic] for any person to have and keep at any place within this city, shall be seperated [sic] into four stone jugs or tine canisters, which shall not contain more than seven pounds each, on pain of forfeiting all such gunpowder,
--
Keywords: GUN POWDER STORAGE